Effect of the use of different programs of auditory stimulus during pregnancy in memory of newborn hearing. ESSSALUD Yanahuara Hospital III - Armida Angelita Fernández Vásquez (2019)
Currently there are contradictory findings about the effects on the newborn of different stimuli that have been applied in prenatal stimulation programs, there is no system for evaluating their performance in the short medium and long term let duly systematized.The aim of this study was to compare the effects of 3 different auditory stimulation programs on the memory newborn hearing and consequently their findings to standardize and systematize a system for evaluating the effectiveness of the best set of auditory stimuli, avoiding inappropriate practices.For this pilot study , 45 patients were divided into 3 groups: 15 pregnant women with gestational age from 16 weeks (Group 1), 15 pregnant women from 29 weeks (2nd group) 15 immediate postpartum (Group 3).The 45 patients were healthy in clinical and laboratory criteria and had an education level at least 5 of high school.The first group, were trained in prenatal stimulation for 8 sessions of 1 hour and 30 minutes per session, for 2 months, including auditory stimulation techniques Model A, used in the Hospital. Learned techniques were applied 3 times per week (20 mm) at home, and during the last month, 01 once a week until the end of pregnancy. With the participation of the husband eventually. The second group, was trained for 8 sessions of 01 hours and 30 minutes per session, including auditory stimulation techniques Model B. Learned techniques were applied 1 time per day (30 mm) at home, and toward the last month, 3 times per day until the end of gestation. Participated husband. The 3rd group received no training at all. In 3 groups were considered the existence of common sounds like Borbor, maternal heartbeat, cell phone use, baker’s horn used in the last pre-natal checks for studies of electronic fetal monitoring, Measurement of the effect of each of stimuli applied to different groups was made by the Individualized Assessment form for each newborn, containing the items that were part of the stimulation and which related to auditory memory parameters agreed by the literature. It was applied a 48 hours old on average and under specific conditions common The most important findings led us to the following conclusion: The baby recognizes some sounds continuously repeated during the last weeks of gestation (instrumental music, instruments such as maracas, a few voices like those of the mother. This is to say the lack of altering their behavior as continue sleeping, not having accelerated heartbeat or continue to suck unlike the children who did not receive this stimulus react repeatedly waking or frowning or raised.There were no major differences in findings among children in the Plan A and Plan 13, there being influenced by the fact that some started early and others to the last weeks of gestation.The loud noises or strong you are bothersome to the baby, despite having been a consistent part of their sound environment, to tell of their responses (frown, mourn or move) recognizing them as stress responses to sound stimuli) More tolerant kind musical instruments on the rain stick rattle, Children are encouraged to instrumental music of the best receivers spoken voice, to say the look of the issuer of the same. In some children, their father’s voice was rising breast sucking, not being a common finding, so no one could generalize The lullaby song produces more intense suction caressing if accompanied by mother, regardless of being stimulated or not in pregnancy